Management Of State High School Teachers In Improving The Quality Of Online Learning During The Covid-19 Pandemic - Abdul Lani; Toni Herlambang; Nursaid Nursaid (Universitas Muhammadiyah Jember, 2021)
The Covid-19 pandemic has caused new paradigms and changes in lifestyle in various aspects of life, including education. The Covid-19 pandemic changed the learning system that was previously carried out face-to-face, after the Covid-19 outbreak, learning had to be done online (online). This condition is undoubtedly a challenge for each school to continue the learning process. As a teacher, you must have a professional attitude and continue to innovate learning in various conditions. This study aims to analyze the effect of professionalism and mastery of technology for public high school teachers on the quality of online learning during the Covid-19 pandemic with a case study at a public high school in Lumajang Subistrict, Lumajang Subdistrict. The methods used to analyze this research include descriptive analysis, test the validity and reliability of the instrument and analysis of Structural Equation Modeling-Partial Least Square (SEM-PLS). The results of this study indicate that professionalism, mastery of learning technology, and teacher performance have a positive and significant influence on the quality of online learning at SMA Negeri in Lumajang Subdistrict, Lumajang District.